Handbook of the geographies of religion - KONG, Lily (Institutional Knowledge at Singapore Management University, 2024)
This international and interdisciplinary handbook offers a comprehensive and an in-depth overview of contemporary research, theory, and practice in the geographies of religion in various parts of the world and with different populations. The book showcases the major theoretical interventions in the field and the debates about the existential constitution of sacred space and what this means for secularization. It outlines the most significant geographical themes related to these new developments, with their implications for how to think about landscapes, space, bodies, and worlds. The book also discusses the future of the field, especially in the realms of encounters and ethics, economies and markets, institutions and organisations, movements and migrations, and media and mediums. It also offers views from disciplines outside of geography, including from sociology, anthropology, religious studies, and media and communications, which demonstrates the contributions of geographers of religion to wider intellectual conversations and debates.